Employment Systems in Japan's Financial Industry: Globalization, Growing Divergence and Institutional Change. (27th November 2015) - Yamauchi, Mari
Abstract: This article examines growing divergence and change in the employment systems of Japan's financial industry from the early 1990s until shortly after the so‐called Lehman Shock. This was a period which saw accelerated deregulation and globalization strongly impact the country's financial markets, leading to intensified competition over human resources. Foreign multinational corporations introduced into Japan's local product and labour markets new global 'rules of the game'; in response, some native firms were forced to alter core aspects of a traditional employment model. The result was the emergence of diverging patterns of employment. The present study will demonstrate that the interaction of two key factors — national ownership and variation among core products and services offered — is shaping employment diversification, mediated by firms' individual policies and practices. This research contributes to the debate on the effects of globalization on the divergence and change of employment systems.